Clinical and epidemiological aspects of gestational syphilis in northern Brazil - Oliveira, Nágylla Alves de; Mendes, Mayza Ribeiro; Feitosa, Maria Aparecida Lima; Neres , Liberta Lamarta Favoritto García (Seven Editora, 2023)
Syphilis is an infectious disease exclusive to humans, caused by a bacterial etiological agent of the species Treponema pallidum. Its main route of transmission is sexual and due to its pathophysiology, it presents several clinical manifestations. Among its classifications, there is congenital syphilis, a problem of interest to public health, due to its ability to trigger serious complications for the fetus and newborn. Thus, the measurement and monitoring of congenital syphilis are of interest for epidemiological surveillance, with notification being compulsory, as notification forms provide information that allows analyzing the effectiveness of prevention, detection and treatment strategies for the disease. These data can be used to guide public health policies, improve prenatal care, and develop more effective prevention measures to reduce rates of congenital syphilis. This epidemiological analysis of the disease evaluated the social and demographic profile of users of the Unified Health System (SUS), affected by gestational syphilis in the Brazilian population in the North region, based on data from the Notifiable Diseases Information System (SINAN), in a period of four years, between 2018 and 2021. To collect the data, the information available in the TABNET software, from the Department of Informatics of the Unified Health System (DATASUS), was used. To conduct this study, data regarding age group, race, education and performance of treponemal and non-treponemal tests were analyzed. After analyzing the data, it was observed that the 3 main reporters of the problem are Pará, Amazonas and Acre, respectively. The profile of the most affected pregnant women is mixed race, with low education, between 20-39 years old. Given the theoretical support and research results, the study concluded that it is important to highlight the importance of gestational syphilis and its impact on public health due to the risk it represents for pregnant women and their babies. It was also noted, according to the theoretical support consulted, the need to understand the epidemiological profile in each region, as it is essential to create or improve prevention and control strategies according to regional needs. DOI:https://doi.org/10.56238/sevened2023.006-090